2014
DOI: 10.1002/2013pa002524
|View full text |Cite
|
Sign up to set email alerts
|

A reconstruction of sea surface temperature variability in the southeastern Gulf of Mexico from 1734 to 2008 C.E. using cross‐dated Sr/Ca records from the coral Siderastrea siderea

Abstract: This study uses skeletal variations in coral Sr/Ca from three Siderastrea siderea coral colonies within the Dry Tortugas National Park in the southeastern Gulf of Mexico (24°42′N, 82°48′W) to reconstruct monthly sea surface temperature (SST) variations from 1734 to 2008 Common Era (C.E.). Calibration and verification of the replicated coral Sr/Ca-SST reconstruction with local, regional, and historical temperature records reveals that this proxy-temperature relationship is stable back to 1879 C.E. The coral SST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(125 citation statements)
references
References 106 publications
10
111
3
Order By: Relevance
“…However, the inconsistent occurrence of massive Porites colonies necessitates the use of additional genera for climate reconstructions. Developments in the use of alternate coral genera as paleoenvironmental indicators have seen recent advances [e.g., DeLong et al, 2014;Felis et al, 2014;, including the potential use of inter-branch skeleton in Acropora , a highly abundant coral genus in many Indo-Pacific reef cores Humblet et al, 2015;Shirai et al, 2008] with significant volumes recovered in IODP Expeditions 310, Tahiti Sea Level [Camoin et al, 2007], and 325, Great Barrier Reef Environmental Changes . recently reported that the inter-branch skeleton of corymbose Acropora colonies (i.e., colonies with branches that initiate from a central location and extend to a common level ) does not display the significant levels of secondary skeletal thickening typically associated with branches, which previously prevented the use of Acropora in high resolution geochemical climate 154 reconstructions Shirai et al, 2008].…”
Section: Reef Coring Techniques Such As Those Employed By the Internmentioning
confidence: 99%
“…However, the inconsistent occurrence of massive Porites colonies necessitates the use of additional genera for climate reconstructions. Developments in the use of alternate coral genera as paleoenvironmental indicators have seen recent advances [e.g., DeLong et al, 2014;Felis et al, 2014;, including the potential use of inter-branch skeleton in Acropora , a highly abundant coral genus in many Indo-Pacific reef cores Humblet et al, 2015;Shirai et al, 2008] with significant volumes recovered in IODP Expeditions 310, Tahiti Sea Level [Camoin et al, 2007], and 325, Great Barrier Reef Environmental Changes . recently reported that the inter-branch skeleton of corymbose Acropora colonies (i.e., colonies with branches that initiate from a central location and extend to a common level ) does not display the significant levels of secondary skeletal thickening typically associated with branches, which previously prevented the use of Acropora in high resolution geochemical climate 154 reconstructions Shirai et al, 2008].…”
Section: Reef Coring Techniques Such As Those Employed By the Internmentioning
confidence: 99%
“…The skeletons of long-lived, massive coral colonies have the potential to produce high-resolution records of past tropical ocean temperatures [Gagan et al, 2000;DeLong et al, 2014;Linsley et al, 2015]. The thin layer of living coral tissue continually precipitates an aragonite (CaCO 3 ) skeleton allowing the coral colony to grow upward and preserve its older skeleton below [Cohen and McConnaughey, 2003].…”
Section: Coral Paleoceanographymentioning
confidence: 99%
“…High latitude cooling has been constrained to 1-2 ˚C [Overpeck et al, 1997;Marcott et al, 2013] but previous Sr/Ca derived estimates of LIA cooling from this region range from 0 to 5 ˚C [Haase-Schramm et al, 2003;DeLong et al, 2014]. The cold end of these estimates implies greater climate sensitivity in the tropics than at high latitudes, conflicting with evidence from both simulations [Holland and Bitz, 2003;Landrum et al, 2013] and 20 th century observations [Pithan and Mauritsen, 2014].…”
Section: Thesis Objectivesmentioning
confidence: 99%
See 2 more Smart Citations